2008
DOI: 10.1093/wjaf/23.2.69
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Stream Channel Morphology Caused by Replacing Road-Stream Crossings on Timber Harvesting Plans in Northwestern California

Abstract: Past studies have shown that roads used for timber management and recreation are major sources of sedimentation in many streams throughout the Pacific Northwestern United States. Stream crossings are portals for the entry of sediment derived from road surface erosion. They are also prone to catastrophic failure during stressing weather events if they are undersized or otherwise deficient in design or construction. In recent years, public and private landowners have replaced or removed numerous deficient crossi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
8
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 5 publications
0
8
0
Order By: Relevance
“…Permanent haul roads are also more expensive to cover with stone. However, Harris et al (2008) found that aggressive use of a combination of armor, silt fences, water control, and erosion vegetation practically eliminated water quality concerns associated with 30 stream crossings on public lands in California.…”
Section: Stream Crossing Type Nmentioning
confidence: 99%
See 2 more Smart Citations
“…Permanent haul roads are also more expensive to cover with stone. However, Harris et al (2008) found that aggressive use of a combination of armor, silt fences, water control, and erosion vegetation practically eliminated water quality concerns associated with 30 stream crossings on public lands in California.…”
Section: Stream Crossing Type Nmentioning
confidence: 99%
“…tream crossings are often considered to be the forest road segment with the greatest potential to introduce sediment into streams (Rothwell 1983, Swift 1985, Milauskas 1988, Aust and Blinn 2004, Harris et al 2008. Typical stream crossings found on current timber harvest operations include fords, culverts, and bridges (Brinker 1997, Blinn et al 1998, Aust et al 2003.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Also, on some horizontal curves, the superelevation is in opposite position to the ditch (Figure 4D). Harris et al (2008) introduced a longitudinal profile as one of the most important factors in decision-making. Using the analysis of microtopography (Figure 3) it can be obtained that we can use waterfronts No.…”
Section: Resultsmentioning
confidence: 99%
“…Harris et al. () found that structures replaced in California on sites with extensive erosion control methods recovered significantly within one rainy season.…”
Section: Methodsmentioning
confidence: 99%